Insentif Finansial dan Insentif Non Finansial terhadap Motivasi Kerja Karyawan - Hayani Hayani; Tri Rusilawati Kasisariah; Amaludin Amaludin (IPM2KPE, 2022)
This study aims to determine the effect of financial and non-financial incentives on employee motivation, and the effect of financial and non-financial incentives simultaneously on CV. Sinar Telekom Regency. This research method is descriptive quantitative. The sample in this study amounted to 47 respondents who were distributed to employees of CV. Sinar Telekom Lahat Regency. Data analysis method used is quantitative analysis using validity test, reliability test, normality test, multiple linear regression analysis and average difference test. The results showed that financial incentives had a positive and significant effect on work motivation. This can be seen from the t count > t table (4.793 > 2.015). Non-financial incentives have a positive and significant effect on employee motivation, this can be seen from the t count > t table (2.356 > 2.015). And financial incentives and non-financial incentives simultaneously have a positive and significant effect on employee motivation. This can be seen from the calculated F value > F table (44.227 > 3.23) and the significance value < significance level (Î±) 0.05 (0.000 <0.05). In conclusion, financial incentives have a positive and significant effect on work motivation. Non-financial incentives have a positive and significant effect on employee motivation. Financial incentives and non-financial incentives simultaneously have a positive and significant effect on employee motivation. Keywords: Financial Incentives, Non-Financial Incentives, Work Motivation